Effectiveness of COVID-19 Vaccines in the General Population of an Italian Region before and during the Omicron Wave - Cecilia Acuti Martellucci; Maria Elena Flacco; Graziella Soldato; Giuseppe Di Martino; Roberto Carota; Antonio Caponetti; Lamberto Manzoli (Vaccines, 2022)
We performed a cohort analysis of the entire population of Abruzzo, Italy, to evaluate the real-world effectiveness of SARS-CoV-2 vaccines against infection, COVID-19 hospitalization or death, over time and during the Omicron wave. All resident or domiciled subjects were included, and official vaccination, COVID-19, demographic, hospital and co-pay exemption datasets were extracted up to 18 February 2022. Multivariable analyses were adjusted for age, gender, hypertension, diabetes, major cardio- and cerebrovascular events, COPD, kidney diseases, and cancer. During the follow-up (average 244 days), 252,365 subjects received three vaccine doses (of BNT162b2, ChAdOx1 nCoV-19, mRNA-1273 or JNJ-78436735), 684,860 two doses, 29,401 one dose, and 313,068 no dose. Overall, 13.4% of the individuals were infected with SARS-CoV-2 (n = 170,761); 1.1% of them had severe COVID-19, and 0.6% died. Compared with the unvaccinated, those receiving two or three vaccine doses showed an 80% to 90% lower risk of COVID-19 hospitalization or death. Protection decreased during the Omicron wave and six months after the last dose, but it remained substantial. Lethal disease was uncommon during the Omicron wave and in the young population, even among the unvaccinated. Some of the current policies may need a re-evaluation in light of these findings. The results from the Omicron wave will inevitably require confirmation.